ANALISIS KINERJA PENGELOLAAN KEUANGAN DAERAH DI ERA OTONOMI DAERAH KABUPATEN JAYAWIJAYA TAHUN ANGGARAN 2016-2020 - Jutisma Buchary Akbar Jumati; Nur Fadila Nacikit; Kumba Digdowiseiso (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the performance of regional financial management in the era of Regional Autonomy in Jayawijaya Regency, Papua Province, for the 2016-2020 Fiscal Year by using the calculation of the Degree of Decentralization Ratio, the Ratio of Regional Financial Independence, the Ratio of Effectiveness of Local Own Revenue, and the Harmony Ratio as seen through Routine Spending and Development Spending. Jayawijaya Regency's Financial Performance Judging from the Decentralization Degree Ratio it is only 4.88% and we can see from the measurement interval which is at > 10 and shows in the Not Good category, the Regional Financial Independence Ratio gets the Instructive category with a total average of 5.13 %, the PAD Effectiveness Ratio of Jayawijaya Regency is in the Very Effective category with a total average of 115.14% and for the Conformity Ratio of the Routine Expenditure Ratio and the Development Expenditure Ratio, it can be seen from the calculation that the Conformity Ratio of Routine Expenditures of Jayawijaya Regency from 2016-2020 has decreased from year to year in 2016 it was at 48.62% and in 2020 it fell to 40.27% with a total average of 45.17% while for the Jayawijaya District Development Expenditure Ratio which was initially in 2016 it reached 51.38% and in 2022 it will increase to 59.73% with an average value of 54.83%.